(untitled) (Journal of Nepal Geological Society, 2011)
The Lesser Himalaya in central Nepal is a fold-and-thrust belt with a complex stratigraphy and structure. In the present study, detailed geological mapping was carried out in the Mugling-Banspani area based on stratigraphic units proposed by Stocklin and Bhattarai (1977) to reveal the geological setting and lithostratigraphy of the area. The study shows that the area is occupied by the low-grade metasedimentary rocks of the Lower Nawakot Group. However, there are several discrepancies in classification of the rocks of the Lower Nawakot Group and their classification does not correspond with the field realities. The Anpu Quartzite thought to be the oldest unit of the Nawakot Complex laterally joins to the Fagfog Quartzite. Similarly, the Banspani Quartzite and Labdi Phyllite laterally join to the Purebensi Qu artzite and Dandagao n Phyllite, respectively. Si milar ly, the Nourpul Formation is clearly divisible into three members with distinct lithological characteristics. Based on the above facts, a revise d stratigraphic classification has been proposed for the rocks of the Lower Nawakot Group in the Mugling Banspani area. The Lower Nawakot Group can be divided into the oldest Kunchha Formation followed up section by the Fagfog Quartzite ( Anpu Quartzite), Dandagaon Phyllite ( Labdi Phyllite), Nourpul Formation and Dhading Dolomite. The Nourpul Formation comprises three members namely the Purebensi Quartzite, the Amdanda Phyllite and the Labdi Khola Carbonate. The Jalbire Syncline, Mugling Anticline, Aklang Syncline and the Anpu Anticline are the major geological structures of the study area.